Hattrick of H-deficient phenotypes at a tertiary care health center in India - Yashaswi Dhiman; Basanta Khatiwada; Manish Raturi; Dushyant Singh Gaur; Rolika Nautiyal; Himanshu Rawat (Iraqi Journal of Hematology)
H-deficient phenotypes, commonly known as Bombay blood type, have more inclination to be found in the Indian subcontinent, and conventional gold standard tube techniques are still the recommended method to identify them, provided a strict adherence to testing protocol. There is more to these phenotypes than just the bombay blood type. This brief communication highlights the identification of three H-deficient phenotypes from a single center that adhered to standard operating procedures and basic testing methodologies. It emphasizes the requirement of indirect Coombs test with pooled “O” cells with blood grouping of every sample irrespective of the testing platform and also the H antigen typing on encountering any suspicion. These H-deficient individuals may not be as rare as we assume them to be provided there are reframed testing policies. Although international collaborations and databases like the International Society of Blood Transfusion database have made it easier to record and share knowledge on blood types, a National network and registries of these rare phenotypes are essential to make them available to the general population who actually benefit from them.